Rotinas familiares de ribeirinhos amazônicos: uma possibilidade de investigação - SILVA, Simone Souza da Costa (2012)
Family routines have been revealed as an interesting strategy that allows the knowledge not only of its operation, but also the development of its members. Nevertheless, investigating routines constitutes a challenge to researchers interested in this subject, mainly when it is about groups inserted in differentiated cultural contexts. In order to provide a methodological contribution, this work describes an instrument of qualitative investigation (IFR – Inventory of Family Routines). This instrument was used to collect data about the routines of families who live in an Amazonia's riverside community, and whose main feature is the geographical and social isolation. The steps of the instrument construction are presented along with the necessary adaptations and the manner of results organization (FAD – Family Activities Diagram), all of them illustrated through an investigative case.